Artificial Intelligence Revolutionizing Homeopathy: Transforming Healthcare with Technology (Homoeopathy for All, 2025)
The convergence of homeopathy and artificial intelligence (AI) is transforming the landscape of holistic healthcare. Traditionally based on individualized treatment and holistic principles, homeopathy is now integrating AI and IT-driven automation to enhance diagnostic accuracy, streamline clinic management, and optimize patient outcomes.
Keywords: Artificial Intelligence; Revolutionizing Homeopathy; Healthcare; Technology